Leading at the speed of growth : - Catlin, Katherine (Hungry Minds, 2001)
Learn how to take your company to the next level of growth through the stories of over 500 successful entrepreneurs. Developed by the Kauffman Center for Entrepreneurial Leadership, this flagship book introduces a new series on managing growth. The authors expertly guide you through the three stages of entrepreneurial growth: initial growth, rapid growth, and continuous growth. Personal stories told by successful entrepreneurs reveal the hows and whys of evolving as a leader at each stage, identifying red flags, vital signs, and secrets of sustained growth. Become a dynamic leader by using this book as your roadmap to entrepreneurial success.